Science Education in Nigerian Public Universities: Challenges and Way Forward - Izunna Somadina Okwelogu; Ogunode Niyi Jacob; Ayinde Abayomi O (Research Parks Publishers, 2021)
Science education is faced with many problems in the Nigerian public universities and this is affecting the development of science education at the various public universities across the country.This presentation discusses the challenges facing teaching of science education in the Nigerian public universities. Secondary and primary data were sourced and used to support the points raised in the presentation. Inadequate funding, inadequate science lecturers, shortage of infrastructural facilities, Brain-drain, poor research, strike action and corruption were identified as challenges facing the teaching of science education in the Nigerian public universities. Adequate funding of science programme in the public universities, employment of more science lecturers, provision of adequate infrastructural facilities, increasing the funding of research programme in sciences, increasing the salaries of academic staff to prevent brain-drain and to motivate the lecturers, implement agreement reached with the unions in the universities and corruption in the universities should be fought using the various anti-corruption agencies in the country were recommended as the ways forward for the development of science education in Nigeria public universities.